Postoperative leukopenia after cytoreductive surgery and hypertherm intraperitoneal chemotherapy for colorectal carcinomatosis– causes and implication on outcomes in a population-based study - Mattias Lepsenyi; Valentinus Valdimarsson; Nader Algethami; Henrik Thorlacius; Lana Ghanipour; Peter Cashin; Dan Asplund; Elinor Bexe Lindskog; Gabriella Jansson Palmer; Per J Nilsson; Ingvar Syk (World Journal of Surgical Oncology)
Abstract Background Leukocytes have been reported to have tumor stimulating effects in colorectal cancer, among other malignancies. In line with this, earlier research has shown improved disease-free survival in patients with postoperative neutropenia compared to non-neutropenic patients following cytoreductive surgery (CRS) and hypertherm intraperitoneal chemotherapy (HIPEC). Aim To evaluate the impact of postoperative leukopenia after CRS and HIPEC on recurrence rate, survival, and risk of complications. Methods All CRS and HIPEC-procedures for colorectal adenocarcinoma in the national Swedish HIPEC-registry since 2015 and local registries in Uppsala and Malmö since 2003 until December 31st, 2021, were included (n = 921). Patients who did not complete a full CRS and HIPEC procedure (n = 99), had incomplete macroscopic cytoreduction (n = 25) or a lack of information on leukocyte count (n = 213) were excluded, resulting in 584 analyzed cases. Primary outcome was overall recurrence rate. Secondary outcomes were overall survival, recurrence-free survival, and perioperative complications. Results Postoperative leukopenia was observed in 54 (9.2%) cases of which 32 (5.5%) developed severe leukopenia. No differences in patient characteristics were noted between those with or without leukopenia. There were no differences in 3-year recurrence rate, overall survival or 3-year recurrence-free survival, between the groups. Neoadjuvant chemotherapy treatment, HR 1.32 (95% CI: 1.02–1.71), higher PCI-score, HR 1.50 (95% CI: 1.09–2.05) and higher pN-stage HR 2.52 (95% CI: 1.74–3.65) were associated with higher 3-year recurrence rate. 3-year mortality was associated with neoadjuvant chemotherapy treatment, HR 1.82 (95% CI: 1.06–3.11), severe postoperative complication, HR 2.39 (95% CI: 1.39–4.13) and high PCI-score, HR 2.60 (95% CI: 1.31–5.14). Treatment with combined oxaliplatin/irinotecan, HR 12.34 (95% CI: 4.51–33.74) was associated with developing postoperative leukopenia. Longer operation time, HR 2.30 (95% CI: 1.55–3.42), and severe leukopenia, HR 3.50 (95% CI: 1.25–9.77) were associated with postoperative complication. Conclusions Postoperative leukopenia did not impact recurrence rate or long-term survival in a statistically significant manner. Neoadjuvant chemotherapy and high PCI-score were associated with both recurrent disease and mortality within 3 years.